Cytomorphological Study of Choroid Plexus Neoplasms and its Correlation with Histopathology - Kumar, Pamu Pramod; Sushma, Yalavarthi; Aparna, Pagidikalava (Annals of Pathology and Laboratory Medicine, 2018)
Background: Choroid plexus neoplasms are uncommon and constitute 0.3 to 0.6% of all brain tumors and 2 to 4% of brain tumors in children below 15 years. Choroid plexus neoplasms pose considerable treatment challenges. CNS Squash cytology (CSC) helps neurosurgeons immensely in the management of choroid plexus neoplasms. The present study aimed at cytomorphological examination of choroid plexus neoplasms on squash smears and to differentiate them from other papillary neoplasms in that location and to correlate with histopathological details. Methods: Intraoperative squash smears of twelve cases of SOLs (Space Occupying Lesions) of ventricles and cerebellopontine angle were included in the present study. Cytological diagnoses were correlated with MRI diagnosis and histopathological evaluation. Result: The study group included 9 (75%) cases of choroid plexus papilloma (CPP), 03 (25%) cases of choroid plexus carcinoma (CPC). Age range was 3 months to 58 years (mean=20.5 yrs) and had equal sex distribution. The tumors were distributed as follows: lateral ventricle (1; 8.33%), fourth ventricle and fourth ventricle with cerebellopontine angle extension (10; 83.34%), and third ventricle (1; 8.33%). Conclusion: Histopathological examination is gold standard in differentiating choroid plexus neoplasms from other papillary neoplasms like Ependymoma and Metastatic adenocarcinoma.